1984
DOI: 10.1128/jb.157.1.134-142.1984
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Rhizobium meliloti pSym genes into Agrobacterium tumefaciens: host-specific nodulation by atypical infection

Abstract: The pSym megaplasmid of Rhizobium meliloti 2011 mobilized by plasmid RP4, or plasmid pGMI42, an RP4-prime derivative which carries a 290-kilobase pSym fragment including nitrogenase and nod genes, was introduced into Agrobacterium tumefaciens. The resulting transconjugants induced root deformations specifically on the homologous hosts Medicago sativa and Melilotus alba and not on the heterologous hosts Trifolium pratense and Trifolium repens. The root deformations were shown to be genuine nodules by physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
3

Year Published

1985
1985
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(31 citation statements)
references
References 34 publications
2
26
0
3
Order By: Relevance
“…That cortical cell divisions could be induced from a distance was concluded earlier from microscopy studies of the first observable plant responses following inoculation (Calvert et al, 1984;Dudley, Jacobs, and Long, 1987) as well as from studies of nodules induced by noninvasive mutants or heterologous, Sym-plasmid carrying strains (Truchet et al, 1980;Hirsch et al, 1984;Truchet et al, 1984;Finan et al, 1985). Bauer et al (1985) showed, by seria1 sectioning, that cell divisions could be induced in the host root cortex by the homologous Rhizobium even though physical contact was prevented by an interposed Millipore membrane, but they did not mention whether empty nodules were formed.…”
Section: Discussion Lnfection Thread Formation Of Alfalfa Nodules 1smentioning
confidence: 82%
“…That cortical cell divisions could be induced from a distance was concluded earlier from microscopy studies of the first observable plant responses following inoculation (Calvert et al, 1984;Dudley, Jacobs, and Long, 1987) as well as from studies of nodules induced by noninvasive mutants or heterologous, Sym-plasmid carrying strains (Truchet et al, 1980;Hirsch et al, 1984;Truchet et al, 1984;Finan et al, 1985). Bauer et al (1985) showed, by seria1 sectioning, that cell divisions could be induced in the host root cortex by the homologous Rhizobium even though physical contact was prevented by an interposed Millipore membrane, but they did not mention whether empty nodules were formed.…”
Section: Discussion Lnfection Thread Formation Of Alfalfa Nodules 1smentioning
confidence: 82%
“…However, alfalfa roots are more susceptible than many other legumes to agents that elicit the formation of ineffective, bacteria-free nodules. R. meliloti mutants defective in ex- (Finan et al, 1985;Leigh et al, 1987) and Agrobacterium tumefaciens transconjugants carrying R. meliloti nodulation genes (Wong et al, 1983;Truchet et al, 1984;Hirsch et al, 1984Hirsch et al, ,1985 induce nodules that superficially resemble normal, nitrogen-fixing nodules. They have a central tissue surrounded by nodule parenchyma and peripheral vascular bundles, but cells of the central tissue are devoid of bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Transfer of these plasmids (or subcloned regions of them) to appropriate strains o( Rhizobium or Agrobacterium can result in concomitant transfer of host-specific nodulation (Johnston etal., 1978;Hooykaas ef at., 1981;Kondorosi ef al., 1982;Wong ef Received 10 August, 1987;revised 23 October, 1987, tFor correspondence. al., 1983Downie ef al., 1983;Schofield ef ai, 1984;Truchet et a/., 1984;Fisher ef a/., 1985).…”
Section: Introductionmentioning
confidence: 99%